PENGARUH LIVE STREAMING SHOPPING TERHADAP IMPULSE BUYING KONSUMEN PADA PLATFORM TIKTOK SHOP - Novia Susanti; Budi Ismanto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This article examines the effect of live streaming shopping on consumers' impulse buying on TikTok Shop through a structured literature review. The review maps empirical studies on live-stream commerce, social presence, perceived value, enjoyment, trust, customer engagement, and impulse buying. Sources were selected based on construct relevance, online-shopping context, and the clarity of their methods and findings. The synthesis indicates that live streaming shopping acts as a compound stimulus that combines product demonstration, real-time seller responses, viewer interaction, and time-limited offers. These stimuli shape cognitive and affective responses, particularly social presence, perceived value, enjoyment, trust, and engagement. Such internal responses can strengthen the urge to buy and shorten consumers' evaluation process before checkout. The relationship is not automatic. Self-control, product need, shopping experience, perceived risk, and information transparency can strengthen or weaken impulse buying. The article proposes a stimulus-organism-response framework and a quantitative research agenda for examining mediation and moderation mechanisms among TikTok Shop users in Indonesia.